Occurrence of traumatic dental injury in cases of domestic violence - Garbin, Clea Adas Saliba [UNESP]; e Queiroz, Ana Paula Dossi de Guimarães [UNESP]; Rovida, Tânia Adas Saliba [UNESP]; Garbin, Artênio José Ísper [UNESP] (FapUNIFESP (SciELO), 2012)
The purpose of this study was to investigate the prevalence and types of traumatic dental injuries in situations of domestic violence. A coross-sectional study was conducted and data were collected from the police occurrence records to domestic physical aggression between 2001 and 2005. Of the 1,844 subjects who underwent medical evaluation, 15 had information pertaining to traumatic dental injuries. From the medical records, the forensic medical reports completed by the forensic medical experts who examined the victims after the aggression were reviewed and data of individuals with dental injuries (e.g., fractures, luxation and avulsion) were collected. In the selected sample, there was a predominance of individuals with injuries to the head and neck region (38.7%), and the frequency of traumatic dental injuries among all injuries to the head and neck region was 2.0%. The most frequently injured teeth were the maxillary incisors (31.8%), followed by the mandibular incisors (27.3%) and the maxillary canines (9.1%). In 31.8% of the injured teeth, the forensic experts did not specify the nomenclature. Of the dental trauma cases, 59.1% were fractures, 27.2% were luxations and 13.7% were avulsions. In conclusion, domestic violence was an important etiologic factor of traumatic dental injury. The aggression in all cases occurred in the form of punches and slaps. Fracture was the most common type of traumatic dental injury, and the most frequently injured teeth were the incisors.
Keywords: Forensic dentistry; Traumatic dental injury; Violence; Wounds and injuries; adolescent; adult; Brazil; child; classification; cross-sectional study; dentistry; domestic violence; female; human; male; middle aged; prevalence; review; statistics; tooth injury; Adolescent; Adult; Child; Cross-Sectional Studies; Domestic Violence; Female; Forensic Dentistry; Humans; Male; Middle Aged; Prevalence; Tooth Injuries